2018
DOI: 10.3390/ani8080135
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Learning of Visual Structures in Domestic Chicks

Abstract: Simple SummaryOur aim is to investigate the recognition of the structure of multi-element configurations; one mechanism that supports communicative functions in different species. Cognitive mechanisms involved in this ability might not have evolved specifically for communicative use, but derive from other functions. Thus, it is crucial to study these abilities in species that are not vocal learners and with stimuli from other modalities. We know already that domestic chicks can learn the temporal statistical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 86 publications
2
7
0
Order By: Relevance
“…As in 28 , this could be achieved only by encoding either the co-occurrence frequencies of the sequence elements (i.e., how often two shapes appear together), or the predictive relations within pair elements (i.e., the transitional probabilities between the two shapes) 50 . Overall, these results are consistent with previous infant research 6,9 as well as studies on chicks and other species (e.g., 22,[24][25][26][27] ) highlighting the importance of imprinting research for the uncovering of animals' spontaneous abstraction abilities. www.nature.com/scientificreports/ Importantly, our evidence confirms the pivotal role of sex in determining familiarity or novelty preferences in this species, and its interaction with the chicks' strain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As in 28 , this could be achieved only by encoding either the co-occurrence frequencies of the sequence elements (i.e., how often two shapes appear together), or the predictive relations within pair elements (i.e., the transitional probabilities between the two shapes) 50 . Overall, these results are consistent with previous infant research 6,9 as well as studies on chicks and other species (e.g., 22,[24][25][26][27] ) highlighting the importance of imprinting research for the uncovering of animals' spontaneous abstraction abilities. www.nature.com/scientificreports/ Importantly, our evidence confirms the pivotal role of sex in determining familiarity or novelty preferences in this species, and its interaction with the chicks' strain.…”
Section: Discussionsupporting
confidence: 90%
“…Thanks to the prominent learning mechanism of filial imprinting, species as domestic chicks (Gallus gallus) offer the opportunity to study unsupervised forms of statistical learning, like it is done in human adults and infants. Using imprinting procedures, it has been possible to demonstrate spontaneous sensitivity to spatial arrangements of visual and audiovisual displays [24][25][26][27] . However, chicks' implicit learning capabilities are not limited to spatial regularities.…”
mentioning
confidence: 99%
“…It is not clear, though, which representations and computational mechanisms different species use to encode positional relationships. Comparative studies have just started to address this issue in primates (Grainger et al 2012; Sonnweber et al 2015), rodents (Murphy et al 2004), and avian species (Chen and ten Cate 2017; Chen et al 2014; Ravignani et al 2015; Rosa-Salva et al 2018; Scarf et al 2016). While some studies have shown successful mastery of the intended pattern, others suggest that animals sometimes focus on a different level of granularity (Ravignani et al 2015; Wakita 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that computations operating on serial stimuli can be available also for visual configurations. Along this line, Rosa-Salva et al (2018) have tested the spontaneous abilities of domestic chicks in visual imprinting, showing a preferential encoding for the position of items located at the edges. The similarities and differences in processing visual and acoustic regularities have just started to be explored (review in Milne et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to these features, imprinting has become a model system for memory, learning and social behaviour (Bateson, 1966; Bolhuis, 1991; Horn, 1985, 2004; McCabe, 2013, 2019). In the laboratory, imprinting is studied using well controlled artificial stimuli such as balls, cubes, cylinders or two-dimensional stimuli presented on cardboards or computer screens (Rosa-Salva et al, 2018; Versace, Schill, Nencini, & Vallortigara, 2016; Versace, Spierings, Caffini, ten Cate, & Vallortigara, 2017; Wood & Wood, 2015). These experiments have shown that chicks discriminate subtle differences of the imprinting objects, such as rotation of the features located inside the imprinting object (Vallortigara & Andrew, 1991), the configuration of items that compose the imprinting stimulus (Rosa-Salva et al, 2018) and even the underlying structure of the stimuli independent of their physical appearance (Martinho & Kacelnik, 2016; Versace, Regolin, & Vallortigara, 2006; Versace, Spierings, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%